Analysis of Vegetables Demand by “Warteg” Restaurants in Bandar Lampung City - Nita Paskalia Siregar; Rabiatul Adawiyah; Lina Marlina (Politeknik Negeri Lampung, 2021)
The purpose of this study is to determine and analyze the demand pattern of vegetables (water spinach, cassava leaves, and eggplant) and the factors that affected the demand of vegetables at warteg restaurants in Bandar Lampung City. The location was determined purposely (purposive method). The number of the respondents in this study were 50 warteg restaurants, taken by proportional random sampling methods. Data were collected from December 2020 to February 2021, taken by interview techniques. The data were analyzed using descriptive analysis methods and multiple regression analysis models. The results showed that the average demand for vegetables from warteg restaurant was 8,5 kg of spinach water per week, 7,9 kg of cassava leaves per week and 3 kg of eggplant per week. The average purchase frequency amounted to 3,58 time per week for spinach water, 3,08 time per week for cassava leaves and 1,26 time per week for eggplant. The types of vegetables menu were stir-fried water spinach, cassava curry vegetables, and eggplant sauce. The restaurant owner usually bought the vegetables at the traditional market. Furthermore, factors affecting demand of vegetables are the price of water spinach, the price of cassava leaves, the price of eggplant, the price of tempe, the price of egg, the price of chicken meat, number of restaurant menu, restaurant income and the price of vegetables dishes.